2018
DOI: 10.1097/corr.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Do Postoperative Results Differ in a Randomized Trial Between a Direct Anterior and a Direct Lateral Approach in THA?

Abstract: Level I, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 58 publications
1
86
2
4
Order By: Relevance
“…Two trials comparing the lateral with the posterior approach showed the posterior approach had greater improvement in muscle strength at 1 year (n = 47) [20], and fewer dislocations at an average 3-year follow-up (n = 196) [21]. A recent RCT (n = 164) found the lateral approach was associated with more abductor muscle weakness and worse PROMs, but the anterior approach had more nerve injuries [22]. A systematic review, including 12 RCTs, reported similar risks of dislocation, nerve injury, infection and venous thromboembolism between the posterior approach and the minimally invasive posterior approach [10].…”
Section: Discussionmentioning
confidence: 99%
“…Two trials comparing the lateral with the posterior approach showed the posterior approach had greater improvement in muscle strength at 1 year (n = 47) [20], and fewer dislocations at an average 3-year follow-up (n = 196) [21]. A recent RCT (n = 164) found the lateral approach was associated with more abductor muscle weakness and worse PROMs, but the anterior approach had more nerve injuries [22]. A systematic review, including 12 RCTs, reported similar risks of dislocation, nerve injury, infection and venous thromboembolism between the posterior approach and the minimally invasive posterior approach [10].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies have shown that the DAA is able to provide an excellent overview about the acetabulum and the surrounding osseous pelvic structures, which explains the high accuracy of acetabular component placement that can be achieved when using this approach [35]. The pearls and pitfalls of the DAA have been discussed previously at large and it seems that the DAA is associated with lower dislocation rates when compared to posterior approaches and a reduced rate of Trendelenburg positive patients when compared to lateral approaches [2,3,36]. As we know from the literature, revision hip arthroplasty can result in soft tissue defects and particularly lesions of the abductor apparatus, increasing the risk for dislocation and insufficient muscular stabilization of the pelvis during standing.…”
Section: Discussionmentioning
confidence: 98%
“…In 70% (n = 43) of the hips, this was the first revision, whereas 30% (n = 18) of the hips underwent at least one previous revision (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In 14 hips, the index procedure was performed in the authors' department, while all others were referrals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the direct lateral approach in THA is associated with a limp postoperatively 35,36 and limping is associated with lower PROM scores after THA. 7,36 These findings are similar to ours. The abductor mechanism of the hip was investigated by an experienced physiotherapist performing the Trendelenburg test as described by Hardcastle and Nade.…”
Section: Discussionmentioning
confidence: 99%